Acquisition of Innate Inhibitor Resistance and Mammalian Pathogenicity During Egg Adaptation by the H9N2 Avian Influenza Virus - Lee, Chung-Young; An, Se-Hee; Choi, Jun-Gu; Lee, Youn-Jeong; Kim, Jae-Hong; Kwon, Hyuk-Joon (Frontiers in Microbiology, 2018)
An H9N2 avian influenza A virus (AIV), A/chicken/Korea/01310/2001 (01310-CE20), was established after 20 passages of influenza A/chicken/Korea/01310/2001 (01310-CE2) virus through embryonated chicken eggs (ECEs). As a result of this process, the virus developed highly replicative and pathogenic traits within the ECEs through adaptive mutations in hemagglutinin (HA: T133N, V216G and E439D) and neuraminidase (NA: 18-amino acid deletion and E54D). Here, we also established that 01310-CE20 acquired resistance to innate inhibitors present in the egg white during these passages. To investigate the role of egg-adapted mutations in resistance to innate inhibitors, we generated four PR8-derived recombinant viruses using various gene combinations of HA and NA from 01310-CE2 and 01310-CE20 (rH2N2, rH2N20, rH20N2, and rH20N20). As expected, rH20N20 showed significantly higher replication efficiency in MDCK cells and mouse lungs, and demonstrated greater pathogenicity in mice. In addition, rH20N20 showed higher resistance to innate inhibitors than the other viruses. By using a loss-of-function mutant and receptor-binding assay, we demonstrated that a T133N site directed mutation created an additional N-glycosite at position 133 in rH20N20. Further, this mutation played a crucial role in viral replication and resistance to innate inhibitors by modulating the binding affinities to avian-like and mammalian-like receptors on the host cells and inhibitors. Thus, egg-adapted HA and NA may exacerbate the mammalian pathogenicity of AIVs by defying host innate inhibitors as well as by increasing replication efficiency in mammalian cells.